Taking leave of Damanhur. Deconversion from a magico-esoteric community. (September 2018) - Cardano, Mario; Pannofino, Nicola
This article deals with an aspect of religious behavior that has remained in the shadows, both in the scientific literature and in public discourse: deconversion from New Religious Movements. The article analyses the deconversion from a magico-esoteric community located in Northern Italy: Damanhur. Founded in the 1970s, Damanhur is one of Europe's major spiritual communities that counts about 400 devotees. The article starts with an outline of the process of deconversion, followed by a brief description of the religious organization studied. Lastly, the process of disaffiliation from Damanhur, is reconstructed, through the close reading of twenty narratives of deconversion of former Damanhurians interviewed in 2010. The process of deconversion is analysed, distinguishing four ideal-typical steps that repropose the main results of the research in this field. They are the coming out of a vague and unfocused discomfort; the attempt to deconstruct the discomfort; the opening of a reflexive instance; and the departure from the community.